Violência escolar e gestão na rede pública estadual de São Paulo: análise de uma escola técnica em esportes - Santos, Vitor Claudio dos (2019)
The objective of this study was to analyze how the management of a State technical school in sports faces violence in the school context. For this purpose, it was established as specific objectives, contextualizing violence, characterizing school management and analyzing management in the face of violence at school. A qualitative study was carried out through the analysis of school documents, such as the multiannual Management plan (PPG) and the Rules of Procedure, as well as the application of semi-structured interviews, seeking to identify the perceptions of the team Practices of violence in everyday school life. The data found were analyzed in light, mainly from authors such as Abramovay (2002), Blaya (2002), Charlot (2002), Debarbieux (2001). The results of this research corroborate the literature, with regard to the identification of violence as a cultural phenomenon and that encompasses several spheres of society beyond the walls of the school. The data also make it possible to infer that the collective and participatory action of management is a preponderant factor for coping with violence and characterizes a democratic management that involves the different actors in the process, including the family and the community. But our research brings something unusual, which we had not detected in other studies consulted that is the coherence of the speech of the managers interviewed with the sayings of PPG.